Citrulline as a Biomarker in the Non-human Primate Total- and Partial-body Irradiation Models. Issue 5 (November 2015) - Jones, Jace W.; Bennett, Alexander; Carter, Claire L.; Tudor, Gregory; Hankey, Kim G.; Farese, Ann M.; Booth, Catherine; MacVittie, Thomas J.; Kane, Maureen A.
<x xml:space="preserve">Abstract</x> Abstract The use of plasma citrulline as a biomarker for acute and prolonged gastrointestinal injury via exposure to total- and partial-body irradiation (6 MV LINAC-derived photons; 0.80 Gy min−1) in nonhuman primate models was investigated. The irradiation exposure covered gastrointestinal injuries spanning lethal, mid-lethal, and sub-lethal doses. The acute gastrointestinal injury was assessed via measurement of plasma citrulline and small intestinal histopathology over the first 15 d following radiation exposure and included total-body irradiation at 13.0 Gy, 10.5 Gy, and 7.5 Gy and partial-body irradiation at 11.0 Gy with 5% bone marrow sparing. The dosing schemes of 7.5 Gy total-body irradiation and 11.0 Gy partial-body irradiation included time points out to day 60 and day 180, respectively, which allowed for correlation of plasma citrulline to prolonged gastrointestinal injury and survival. Plasma citrulline values were radiation-dependent for all radiation doses under consideration, with nadir values ranging from 63–80% lower than radiation-naïve NHP plasma. The nadir values were observed at day 5 to 7 post irradiation. Longitudinal plasma citrulline profiles demonstrated prolonged gastrointestinal injury resulting from acute high-dose irradiation had long lasting effects on enterocyte function. Moreover, plasma citrulline did not discriminate between total-body or partial-body irradiation over the first 15 d following irradiation and was not predictive of survival based on the radiation models considered herein.